2018
DOI: 10.1038/s41598-018-23986-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Population Genetic Structure of red swamp crayfish, Procambarus clarkii, in China

Abstract: The red swamp crayfish (Procambarus clarkii) is one of the most economically important farmed aquatic species in China. However, it is also a famous invasive species in the world. This invasive species was dispersed most via human activities including intentional or unintentional carry in China. Thus, P. clarkii naturally distributed in China provides us a desirable mode to investigate the genetic structure of an invasive species dispersed mainly by human-mediated factors. To reveal the impact of human-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 48 publications
(53 reference statements)
0
26
0
1
Order By: Relevance
“…We further speculate that the colonization of the marsh of Mès probably resulted from a secondary introduction event using an inoculum from the marsh of Brière given that the allelic composition of the network of Mès was nested in that of the marsh of Brière. Comparable variations in the levels of genetic diversity between waterbodies were found elsewhere (Huang et al, ; Li et al, ; Paulson & Martin, ; Yi et al, ), but such a fine genetic signal of crayfish spread was not identified, probably blurred by multiple introduction events at several locations and/or recurrent gene flow between populations after crayfish was introduced.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We further speculate that the colonization of the marsh of Mès probably resulted from a secondary introduction event using an inoculum from the marsh of Brière given that the allelic composition of the network of Mès was nested in that of the marsh of Brière. Comparable variations in the levels of genetic diversity between waterbodies were found elsewhere (Huang et al, ; Li et al, ; Paulson & Martin, ; Yi et al, ), but such a fine genetic signal of crayfish spread was not identified, probably blurred by multiple introduction events at several locations and/or recurrent gene flow between populations after crayfish was introduced.…”
Section: Discussionmentioning
confidence: 63%
“…The species acclimatizes to a wide range of aquatic environments, and generally spreads rapidly once introduced (e.g., Capinha, Brotons, & Anastácio, ; Lodge et al, ). Recent studies have investigated the genetic structure of populations of the red swamp crayfish at large spatial scales, and highlighted the predominant role of anthropogenic dispersal in its spread across regions (Huang, Tang, Cai, Lin, & Wu, ; Yi et al, ). Tracking studies have also revealed its capacity to travel several kilometres (Aquiloni, Ilhéu, & Gherardi, ; Barbaresi, Santini, Tricarico, & Gherardi, ; Gherardi & Barbaresi, ; Gherardi, Tricarico, & Ilhéu, ), and to resist desiccation well enough to cross terrestrial habitats (Banha & Anastácio, ; Ramalho & Anastácio, ).…”
Section: Introductionmentioning
confidence: 99%
“…Genome‐wide high‐throughput techniques based on RADseq have been widely used in ascertaining the population genomics of invasive species (Elfekih et al, ; Resh et al, ; Yi et al, ). Nevertheless, the choice of the sample sizes for such studies is generally ad hoc, and related studies are still scarce (Hoban, Gaggiotti, & Bertorelle, ).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide high-throughput techniques based on RADseq have been widely used in ascertaining the population genomics of invasive species (Elfekih et al, 2018;Resh et al, 2018;Yi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most genetic studies of P. clarkii have focused on genetic variability at a regional scale (e.g. Almerão et al., ; Barbaresi, Gherardi, Mengoni, & Souty‐Grosset, ; Quan, Pease, Breinholt, & Wayne, ; Torres & Álvarez, ; Yi et al., ). Of these, very few studies have attempted to unveil the invasion routes and, when performed, they did so only at a regional scale.…”
Section: Introductionmentioning
confidence: 99%